The Cleavage Domain of the Amyloid Precursor Protein Transmembrane Helix Does Not Exhibit Above‐Average Backbone Dynamics. Issue 15 (17th September 2013) - Pester, Oxana; Götz, Alexander; Multhaup, Gerd; Scharnagl, Christina; Langosch, Dieter
<x xml:space="preserve">Abstract</x> Wobbly backbone: The backbone dynamics of the amyloid precursor protein (APP) transmembrane helix was compared to those of other transmembrane domains. In contrast to expectation, no above‐average backbone dynamics was found for the APP transmembrane helix; the dynamics thus appears not to be optimized for cleavage.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>